On the Front Lines of the COVID-19 Pandemic: Occupational Experiences of the Intimate Partner Violence and Sexual Assault Workforce - Wood, Leila; Schrag, Rachel Voth; Baumler, Elizabeth; Hairston, Dixie; Guillot-Wright, Shannon; Torres, Elizabeth; Temple, Jeff R. (Journal of interpersonal violence, 2022)
In the face of increasing risk for intimate partner violence (IPV) and sexual assault during the COVID-19 pandemic, there is an urgent need to understand the experiences of the workforce providing support to survivors, as well as the evolving service delivery methods, shifting safety planning approaches, and occupational stress of frontline workers. We addressed this gap by conducting an online survey of members of IPV and sexual assault workforce using a broad, web-based recruitment strategy. In total, 352 staff from 24 states participated. We collaborated with practitioner networks and anti-violence coalitions to develop the brief survey, which included questions about work and health, safety planning, and stress. We used chi-square, t-test, and ANOVA analysis techniques to analyze differences within position and demographic variables. For qualitative data, we used thematic analysis to analyze responses from four open-ended questions. The sample was majority female-identified (93.7%) and essential workers in dual IPV and sexual assault programs (80.7%). Findings demonstrated that since the pandemic began, IPV and sexual assault staff are experiencing more personal and professional stressors, perceive a decrease in client safety, and lack resources needed to help survivors and themselves. Common problems included a lack of food or supplies at home and work and housing and financial support for survivors. There was a 51% increase in the use of video conference for work, which contributed to workforce strain. Reductions in overall service capacity and a shift to remote service provision have implications for both survivors and staff. These findings suggest a critical need for additional training, infrastructure, and support for the IPV and sexual assault workforce. There is an urgent need to classify IPV and sexual assault staff as first responders and address the occupational stress associated with the COVID-19 pandemic.